Level of Understanding of Football Club Coaches Regarding the Preparation of Physical Training Program. (study on soccer club coaches Bengkulu City) - Andes Permadi (UNIB Press, 2024)
This study aims to determine the level of understanding of soccer club coaches Football Club Coaches Regarding the Preparation of the Bengkulu City Physical Training Program. This study uses the theory of understanding which explains how well a coach understands the physical training program a coach in preparing a physical training program properly and correctly. This research uses qualitative research methods with a descriptive approach. The data collection techniques used in this research are in-depth interviews, observation and documentation. Determination of research informants is done by purposive sampling technique. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. conclusion. The results of this study are the level of understanding of trainers related to compiling a physical training program, only 8 trainers are good with a category of 80% in providing appropriate and structured physical training. in providing appropriate and structured physical exercise.